Labor Market - Evolution and Trends in Post-Pandemic Times - WANG, Jianbo; GHINEA, Raluca-Elena; STATE, Cristina; ZHANG, Xiaoliang (European Journal of Sustainable Development, 2023)
Since the appearance of the first entrepreneurial activities, people have noticed that the most important resource, without which they will not be able to be successful, is the human resource. Over time, industries and fields of activity have evolved and this is obvious to everyone, but this would not have been possible without well-trained, involved and eager people to achieve performance. Therefore, whatever resources are involved in a business, regardless of the field, country, coverage area, the human resource remains the most valuable. The business sector is constantly evolving and, along with it, the labor market also shows a dynamic that is at least directly proportional. The pandemic period strongly affected almost all economic sectors and, at the same time, a very large number of employees were directly affected by these changes: either they became unemployed, or they were laid off, or (the happiest ones) they continued the flow of work, without being strongly affected by what happened in the market. We have analysed these changes at the international level in order to outline the evolution of the labor market in recent years and its future trends. Through this article, with the help of the synthesis of case studies carried out by accredited institutions as well as the specialized literature, we propose to identify what was, with the total or partial return to normality, the dynamics of the labor market and how the companies managed to straighten and fold with the new realities of the markets. Keywords: pandemic, human resources, business growth, crisis, labor market